Pengukur Gula Darah Non-Invasif Berbasis Internet of Things - Nila Novita Sari; Angely Fransiska Kurnia Lazha (Politeknik Negeri Jakarta, 2023)
Diabetes is a chronic disease characterized by high blood sugar levels. Without proper attention and treatment, diabetes can become a deadly disease. It is estimated by the International Diabetes Federation, that by 2045 there will be 28.6 million diabetics in Indonesia. Monitoring blood sugar levels regularly every day can help diabetics continue to monitor blood sugar levels so that they remain within normal limits. Generally checking blood sugar must be passed with an uncomfortable and even painful feeling because a blood sample is needed. The process of taking blood samples is known as an invasive method, namely by pricking a fingertip with a lancet so that blood comes out, then a drop of blood is placed on a test strip and the results will come out on the glucose meter. To facilitate monitoring of blood sugar levels, this research has developed a non-invasive tool that can help diabetics control their blood sugar levels. By utilizing the Near-Infrared Spectroscopy method, the examination will be carried out more comfortably, painlessly, and affordably. This tool, which was built using the Flame Detection Module and ESP32, has been functioning with an error percentage in the tests conducted on 5 volunteers of 17.9%. The output resulting from measuring blood sugar levels will be sent to Telegram application along with the measurement date so that the data can be used as a daily monitoring record.